Creation as an Ecumenical Problem: Renewed Belief through Green Experience - Hughson, Thomas (Theological studies, 2014)
Loss of a sense of creaturehood and of members has occurred across the lines of divided churches in a secular context. The author explores the question whether green experience of nature can be a path toward a renewed sense of creaturehood. Bernard Lonergan’s distinction between faith and belief allows for identifying a primordial faith that interprets the cosmos as numinous. Ignatius of Loyola’s Spiritual Exercises interprets primordial faith with the biblical word of God as Creator. Why not develop local ecumenical experiments in reevangelization that address green experience?